Synthesis of γ-Lactones via the Kowalski Homologation Reaction: Protecting-Group-Free Divergent Total Syntheses of Eupomatilones-2,5,6, and 3- epi-Eupomatilone-6 - Choi, Hosam; Jang, Hanho; Kim, Hyoungsu; Lee, Kiyoun (Organic Letters, 2019)
A highly efficient synthesis of functionalized chiral γ-butyrolactone scaffolds has been described. The basis of the approach is the Kowalski ester homologation that is modified for our proposed transformation. The newly developed methodology combines a divergent synthetic strategy to permit a straightforward protecting-group-free asymmetric total syntheses of eupomatilones-2,5,6, and 3-epi-eupomatilone-6 in five or six steps from commercial starting materials, making it one of the shortest syntheses reported to date.